1993
DOI: 10.7326/0003-4819-119-6-199309150-00010
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Parenteral Antibiotic Treatment of Patients with Fibromyalgia and Fatigue and a Positive Serologic Result for Lyme Disease: A Cost-Effectiveness Analysis

Abstract: For most patients with a positive Lyme antibody titer whose only symptoms are nonspecific myalgia or fatigue the risks and costs of empirical parenteral antibiotic therapy exceed the benefits. Only when the value of patient anxiety about leaving a positive test untreated exceeds the cost of such therapy is the empirical treatment cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(27 citation statements)
references
References 0 publications
1
24
0
2
Order By: Relevance
“…It thus was concluded that Lyme disease may indeed trigger fibromyalgia and may even coexist with that syndrome in a chronic form; however, antibiotic treatment usually fails to resolve the symptoms of fibromyalgia. The relative futility of treating patients with symptoms of fibromyalgia and positive serological results for Lyme disease with antibiotics was further demonstrated by a cost-analysis study which demonstrated that in endemic areas the risks and costs of empirical parenteral antibiotic therapy exceed the benefits [21]. Moreover, in a retrospective analysis of 800 cases of persisting nonspecific musculoskeletal or neurological symptoms thought to represent chronic Lyme disease, 77 patients were found to suffer from fibromyalgia per se and to have received recurrent courses of antibiotics [22].…”
Section: The Tale Of Lyme Diseasementioning
confidence: 96%
“…It thus was concluded that Lyme disease may indeed trigger fibromyalgia and may even coexist with that syndrome in a chronic form; however, antibiotic treatment usually fails to resolve the symptoms of fibromyalgia. The relative futility of treating patients with symptoms of fibromyalgia and positive serological results for Lyme disease with antibiotics was further demonstrated by a cost-analysis study which demonstrated that in endemic areas the risks and costs of empirical parenteral antibiotic therapy exceed the benefits [21]. Moreover, in a retrospective analysis of 800 cases of persisting nonspecific musculoskeletal or neurological symptoms thought to represent chronic Lyme disease, 77 patients were found to suffer from fibromyalgia per se and to have received recurrent courses of antibiotics [22].…”
Section: The Tale Of Lyme Diseasementioning
confidence: 96%
“…In the past, antibiotic therapy of patients with chronic fatigue syndrome who are seropositive but have no autochthonous antibody production in the central nervous system has been considered unnecessary [14]. Lightfoot et al [15]carried out a cost-benefit analysis that indicated that for the majority of patients with a positive Lyme antibody titer whose only symptoms are nonspecific myalgia or fatigue the risks and costs of empirical parenteral antibiotic therapy exceed the benefits. In light of these current results, we believe it is worth examining whether an antibiotic therapy should be considered in patients with chronic fatigue and positive Borrelia serology.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial culture has a poor sensitivity in detecting B. burgdorferi in CSF or synovial fluid. Serological tests are primarily used for microbiological diagnosis, but even good serological tests creates confusion especially in the case of borderline-positive results [11,17]. Recently polymerase chain reaction (PCR) has been increasingly used for detection of B. burgdorferi DNA in various specimens like skin, CSF and synovial fluid in the hope of improving diagnosis and to clarify questions of treatment in less clear situations [5,6,9,13].…”
Section: Introductionmentioning
confidence: 99%